Criminology and war: where are we going and where have we been?. Issue 10 (October 2016) - DiPietro, Stephanie M.
Abstract: Although the metaphor of war (e.g., the war on terror, war on crime, war on drugs) figures prominently in contemporary criminological discourse, criminologists have generally lagged behind other disciplines in studying the reality of war and its implications for crime, punishment, and ideology. In this essay, I first consider potential reasons for criminology's limited role in studying war and make the case for why war warrants a more central place in criminological discourse. Subsequently, I trace some of criminology's early contributions to the study of war in two domains—(a) legal responses to war and (b) the link between war and crime—and reflect upon ways in which the discipline can both broaden its purview and draw from its own intellectual history to engage more critically with the subject of war.